RESOURCE PROVISION OF HOUSEHOLDS IN THE CARPATHIAN REGION OF UKRAINE: THE ASPECT OF SOCIAL VULNERABILITY OF THE POPULATION - MAKHONIUK, Oleksandr; BIDAK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of aspects that affect the social vulnerability of the population of the Carpathian region. The resource provision of domestic households in the focus of social vulnerability was analyzed, which included the analysis of such indicators as wages, income from entrepreneurial activity, protected resources of the social sphere in monetary terms. A review of the available statistical data made it possible to formulate the negative trends that occurred over the last decade in the structure of resource provision of domestic households. The increase in the share of wages in the incomes of households in the Carpathian region is negatively perceived, which is substantiated by relevant explanations. In particular, the general reduction of state social payments to the population was critically assessed, in connection with which significant attention was paid to the definition of the living wage, which serves as the basis for calculating these payments and other state charges. Attention is paid to the issue of preschool education in the Carpathian region; formulated how households with children of preschool age constitute one of the most socially vulnerable groups of the country’s population. The protracted processes of external migration, which are characteristic of the Carpathian region, and which lead unequivocally to destructive demographic distortions in it, are also emphasized. Based on the given data, we can talk about the existence or development of "unhealthy" socio-economic processes that affect the way of life of the local population of the Carpathian region and that will determine the development trends of the region in the nearest medium-term perspective. It is noted that today the issue of social vulnerability of Ukrainians is exacerbated even more by the full-scale war with Russia, so the request to develop a better toolkit for analyzing resource provision and population needs becomes urgent.